-2p+28=6p-44

Simple and best practice solution for -2p+28=6p-44 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p+28=6p-44 equation:


Simplifying
-2p + 28 = 6p + -44

Reorder the terms:
28 + -2p = 6p + -44

Reorder the terms:
28 + -2p = -44 + 6p

Solving
28 + -2p = -44 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
28 + -2p + -6p = -44 + 6p + -6p

Combine like terms: -2p + -6p = -8p
28 + -8p = -44 + 6p + -6p

Combine like terms: 6p + -6p = 0
28 + -8p = -44 + 0
28 + -8p = -44

Add '-28' to each side of the equation.
28 + -28 + -8p = -44 + -28

Combine like terms: 28 + -28 = 0
0 + -8p = -44 + -28
-8p = -44 + -28

Combine like terms: -44 + -28 = -72
-8p = -72

Divide each side by '-8'.
p = 9

Simplifying
p = 9

See similar equations:

| -6(x+2)-13=10+1 | | (-10x+35)*(5)=x | | 9t=42 | | 9(-8)-4((-8)-7)= | | -2x+7+7x=-3 | | -65+2x=33-5x | | 7c-4c=78+12 | | 34-5x=-21 | | 6y-90=5y-75 | | 5(t-6)+5t=5(2t+2)-9 | | (-10x+35)*(5)= | | (6-2c)+(3c-4)= | | 0.5+0.7=-0.75 | | 4h=5h-60 | | 3x+18=4x+13 | | y=(2t(5-t)) | | 150m-100m+42750=45450-175m | | 3m+167=4m+55 | | 21=6+x+-4x | | 2.3p=46 | | 5x-7=3x+27 | | 0.7x-2.1=1.5x+2.7 | | -3(8x+10)=6(-4x-14) | | 5(v+7)+7v=23 | | 5j+33=18 | | (-3)(2x-5)-8=7-x | | 20-0.5x=21 | | 4b-6-12b-5= | | (x-3)(x-3)=36 | | 4(u-6)+3u=32 | | 6(7a-1)=8(4a+11) | | 14=7x+4-2x |

Equations solver categories